Zabala, Santiago (2017). Why only art can save us: Aesthetics and the absence of emergency - Riba, Jordi (Enrahonar. An international journal of theoretical and practical reason, 2019)
Zabala, Santiago (2017) Why only art can save us: Aesthetics and the absence of emergency Nova York: Columbia University Press, 216 p. ISBN 978-0231183499